Job of Suburbia? A Serious Man and Viewer Perceptions of the Biblical - Tollerton, David C. (The journal of religion and film, 2011)
In the short period since its release in 2009, the notion that A Serious Man represents a retelling of the Book of Job has gained great currency. This is the case despite the film’s makers, Joel and Ethan Coen, denying that the biblical tale was their inspiration. This article considers the relationship between Job and A Serious Man and the motivations that may lie behind the assertion of parallels between the two. It is ultimately suggested that the relationship between film and text is more substantial if we look beyond the partial plot similarities to the theme of theological absurdity that both explore.